2023
DOI: 10.1186/s12889-023-16168-8
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative social disadvantage and health-related quality of life: national health interview survey 2013–2017

Kobina Hagan,
Zulqarnain Javed,
Miguel Cainzos-Achirica
et al.

Abstract: Background Evidence for the association between social determinants of health (SDoH) and health-related quality of life (HRQoL) is largely based on single SDoH measures, with limited evaluation of cumulative social disadvantage. We examined the association between cumulative social disadvantage and the Health and Activity Limitation Index (HALex). Methods Using adult data from the National Health Interview Survey (2013–2017), we created a cumulativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(64 reference statements)
0
3
0
Order By: Relevance
“… 25 26 A comprehensive SDOH index, as used in this study, may inform future development of holistic social risk assessment approaches and evidence-based, individualized social support interventions. 27 In contrast to prior reports, ours is the first nationally representative study to comprehensively describe the burden of social disadvantage experienced by adults with diabetes and the extent to which it predicts mortality in this population. We found that, at each SDOH quartile, people with diabetes faced 1.5-fold to 2-fold higher AAMR than people without diabetes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 25 26 A comprehensive SDOH index, as used in this study, may inform future development of holistic social risk assessment approaches and evidence-based, individualized social support interventions. 27 In contrast to prior reports, ours is the first nationally representative study to comprehensively describe the burden of social disadvantage experienced by adults with diabetes and the extent to which it predicts mortality in this population. We found that, at each SDOH quartile, people with diabetes faced 1.5-fold to 2-fold higher AAMR than people without diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, prior work assessing aggregate SDOH burden and clinical outcomes is primarily based on a relatively small number of SDOH, is focused on the general population or defined clinical subgroups other than diabetes, or assesses non-mortality outcomes 25 26. A comprehensive SDOH index, as used in this study, may inform future development of holistic social risk assessment approaches and evidence-based, individualized social support interventions 27. In contrast to prior reports, ours is the first nationally representative study to comprehensively describe the burden of social disadvantage experienced by adults with diabetes and the extent to which it predicts mortality in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (2023) defines SDOH as the conditions in the environments where people are born, live, learn, work, play, worship, and age that affect a wide range of health, functioning, and quality-of-life outcomes and risks. SDOH potentiate disproportionate disease burden among historically marginalized communities (Hagan et al, 2023). For example, several measures of social vulnerability and SDOH illustrate the challenges faced by Hispanic/Latino communities in San Diego County.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%